Program Market Day sebagai Stimulus untuk Mengembangkan Karakter Kewirausahaan Murid Sekolah Dasar - Hanama, Akhmad; Kristiawan, Yusie; Siswanto, Deny Hadi; Syah, Arga Bagus Pratama Dyah Aan Firman (Prodi PGMI STAI Sabili Bandung, 2024)
This study aims to reveal the character values of students integrated into entrepreneurship education through the Market Day program, using a qualitative research method with a case study design. The results show that this entrepreneurial activity fosters character values such as innovation, creativity, responsibility, cooperation, and self-confidence. Another interesting finding is the use of various languages in communication, including Indonesian, English, and Javanese. The conclusion of this study indicates that the Market Day program, implemented intensively in schools, provides students with the foundation to optimally internalize entrepreneurial character values. The Market Day program conducted at Muhammadiyah Pulokadang Elementary School also plays a role in establishing transactional patterns that encourage students to actively communicate while selling